THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT IN THE DIRECTORATE GENERAL OF TAXES OF NORTH SUMATRA I KPP PRATAMA MEDAN TIMUR - Sheila Galuh Syafira Siregar; Prihatin Lumbanraja; Amlys Syahputra Silalahi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The performance of the employees at the KPP Pratama Medan Timur has not reached optimal results in recent years, as can be seen in the fluctuating realization of tax revenues. In order to improve employee performance at the tax office, good transformational leadership is needed, capable of motivating employees to give their maximum abilities. Additionally, support from the institution is equally important in increasing employee engagement in their work. This research aims to determine and analyze the influence of transformational leadership and perceived organizational support on employee performance through employee engagement at the Directorate General Of Taxes Of North Sumatra I KPP Pratama Medan Timur. This research is quantitative descriptive research. The population in this study is all structural employees at the KPP Pratama Medan Timur, totaling 84 employees. The sample used is a saturated sample where all populations are taken as samples. The data analysis used is Structural Equation Modeling. The results of this study indicate that transformational leadership does not directly affect employee performance significantly, while perceived organizational support has a positive and significant direct effect on employee performance. Then, transformational leadership and perceived organizational support directly have a positive and significant effect on employee engagement, and employee engagement directly has a positive and significant effect on employee performance. Indirectly, transformational leadership and perceived organizational support have a positive and significant effect on employee performance at the KPP Pratama Medan Timur, mediated by employee engagement.